AN ANALYSIS TYPE OF PLOT INCREDIBLES 2 MOVIE - Adinda Alysiha; Yeni Probowati; Surya Priyambudi (Fakultas Bahasa & Sastra Universitas Wijaya Putra, 2023)
As part of this inquiry, the researcher evaluated the plot type of Incredibles 2, which was released in 2018. This study is to determine the many sorts of storylines that were employed by the writer in the motion picture The Incredibles 2 (also known as “Incredibles 2”), which is also known as “Incredibles 2.” The researcher employed descriptive approaches in order to describe and analyze the data that was obtained for this study. In order to gain a detailed description of the storyline in this movie, the researcher used a qualitative approach, and he or she also used descriptive techniques. The researcher continues by putting Robert Stanton’s notion about the storyline into practice. During the course of this investigation, the researcher came across four unique sets of pictures, namely two picture flashback charts. The researcher may come to the following conclusion after going through all of the information and analyzing it, because the events of the story take place of the data analysis, the author participates that the reader will have a better comprehension of the storyline of the movie Incredibles 2 after reading this research. The author thinks that the study that is offered here will be helpful to other readers as a resource for plot analysis.